Biodistribution of thiamphenicol following intravenous administration in goats - KUMAR, VINOD; VERMA, S P; RANA, R D; PANGHAL, R S (The Indian Journal of Animal Sciences, 2011)
The distribution of thiamphenicol (TAP) in various body fluids and tissues of goats was determined by administering thian1phenicol as 30% solution in N, N-dimethylacetamide through intravenous route. The TAP level in plasma was detected to be 25.14Â±1.73 Ilg/m1 at the time of sacrifice. The level was very high in urine. In kidney and bile, the level was more than double the level of plasma. In liver, prostate gland and urinary bladder the level of TAP was higher than the level in plasma. In ileum thy level was detected slightly lesser than 15 llg/g of tissue. The drug could not be detected in brain, testes, epididymous, adrenal gland, adipose tissue, aqueous humour, vitreous humour and cerebrospinal fluid. The TAP seems to be distributed in ahnost all body tissues/ organs of goat and thus the drug may be used successfully for treating the systemic infections sensitive to TAP except for eNS and eye infections.Â